The Boat Design and Prototype For Waste Management in the Banjir Kanal Timur (BKT) Jakarta - Arif Fadillah; Yudha Kurniawan Santosa; Adam Adrian; Putra Pratama; Augustinus Pusaka; Y. Arya Dewanto (JEPTIRA, 2025)
The Ujung Menteng East Flood Canal is one of the objects that is still lacking in efforts to prevent river pollution. Therefore, to overcome this problem, an environmentally friendly waste management boat is designed by using electric power for the boat's electrical equipment needs and propulsion. By analyzing the resistance, stability using Maxsurf Software, the size of the garbage boat is obtained, namely LOA = 5.50 m, LPP = 4.825, B = 2.30 m, H = 1.10 m and T = 0.27 m, with uses 2 batteries for propulsion and conveyors, and 12 solar panels. This boat has a crew of 3 people. made a prototype boat handling environmentally friendly waste by using electric power for the needs of boat electrical equipment and propulsion. By selecting materials using the SWOT method. The purpose of making this boat prototype is to make a waste management boat based on renewable energy and to make an environmentally friendly garbage boat.